Limited use of virtual reality in primary care physiotherapy for patients with chronic pain - Syl Slatman; J. Bart Staal; Harry van Goor; Raymond Ostelo; Remko Soer; Jesper Knoop (BMC Musculoskeletal Disorders, 2024)
Abstract Background Chronic pain is a disabling condition which is prevalent in about 20% of the adult population. Physiotherapy is the most common non-pharmacological treatment option for chronic pain, but often demonstrates unsatisfactory outcomes. Virtual Reality (VR) may offer the opportunity to complement physiotherapy treatment. As VR has only recently been introduced in physiotherapy care, it is unknown to what extent VR is used and how it is valued by physiotherapists. The aim of this study was to analyse physiotherapists’ current usage of, experiences with and physiotherapist characteristics associated with applying therapeutic VR for chronic pain rehabilitation in Dutch primary care physiotherapy. Methods This online survey applied two rounds of recruitment: a random sampling round (873 physiotherapists invited, of which 245 (28%) were included) and a purposive sampling round (20 physiotherapists using VR included). Survey results were reported descriptively and physiotherapist characteristics associated with VR use were examined using multivariable logistic regression analysis. Results In total, 265 physiotherapists participated in this survey study. Approximately 7% of physiotherapists reported using therapeutic VR for patients with chronic pain. On average, physiotherapists rated their overall experience with therapeutic VR at 7.0 and “whether they would recommend it” at 7.2, both on a 0–10 scale. Most physiotherapists (71%) who use therapeutic VR started using it less than two years ago and use it for a small proportion of their patients with chronic pain. Physiotherapists use therapeutic VR for a variety of conditions, including generalized (55%), neck (45%) and lumbar (37%) chronic pain. Physiotherapists use therapeutic VR mostly to reduce pain (68%), improve coordination (50%) and increase physical mobility (45%). Use of therapeutic VR was associated with a larger physiotherapy practice (OR = 2.38, 95% CI [1.14–4.98]). Unfamiliarity with VR seemed to be the primary reason for not using VR. Discussion Therapeutic VR for patients with chronic pain is in its infancy in Dutch primary care physiotherapy practice as only a small minority uses VR. Physiotherapists that use therapeutic VR are modestly positive about the technology, with large heterogeneity between treatment goals, methods of administering VR, proposed working mechanisms and chronic pain conditions to treat.